2000
DOI: 10.1002/(sici)1097-4644(2000)77:34+<61::aid-jcb11>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of genes by tumor cells of a low or a high malignancy phenotype: The case of murine and human Ly-6 proteins

Abstract: Progression of tumor cells toward a high malignancy phenotype and metastasis is a multi-event cascade involving inter alia alterations in the expression of various genes. The focus of our laboratory is on genes whose altered expression may lead, directly or indirectly, to an increased malignancy phenotype. The identification of such genes and the evaluation of the consequences of their altered expression is essential for attempts to halt tumor progression and prevent metastasis formation. Published work origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 34 publications
0
15
0
1
Order By: Relevance
“…Induction of the TGF-b induced protease furin, which converts latent TGF-b to an active cytokine (Dubois et al, 2001), may contribute to the maintenance of the autocrine TGF-b loop. Furthermore, Ly6a.2, a cell surface marker particularly enriched on metastatic cells (Witz, 2000), was sharply increased (>50-fold) after prolonged TGFb1 treatment. Changes in integrin patterning displayed upregulation of the fibronectin receptor subunit integrin b1 and the concerted decrease of the parenchymalenriched isoform integrin b4.…”
Section: Resultsmentioning
confidence: 99%
“…Induction of the TGF-b induced protease furin, which converts latent TGF-b to an active cytokine (Dubois et al, 2001), may contribute to the maintenance of the autocrine TGF-b loop. Furthermore, Ly6a.2, a cell surface marker particularly enriched on metastatic cells (Witz, 2000), was sharply increased (>50-fold) after prolonged TGFb1 treatment. Changes in integrin patterning displayed upregulation of the fibronectin receptor subunit integrin b1 and the concerted decrease of the parenchymalenriched isoform integrin b4.…”
Section: Resultsmentioning
confidence: 99%
“…We observed overexpression of minopontin (osteopontin), RRM2 and Ly6d in small tumours of EGF2B mice. Overexpression of the latter genes was observed in human cancers and correlated with invasiveness and metastatic potential (Chen et al, 2000;Witz, 2000;Gotoh et al, 2002).…”
Section: Transcript Profilingmentioning
confidence: 99%
“…A previous study indicated that the upregulated expression of Sca-1 is associated with a more destructive tumor phenotype (25). Furthermore, in mouse models, Sca-1 has been shown to be associated with greater tumorigenic potential (26).…”
Section: Discussionmentioning
confidence: 98%